Knowledge Shift Model of Strategic Alliance Based on Prisoner's Dilemma and Snowdrift Game - Ai Hong Shan; Zhang Yabin (Institute of Advanced Engineering and Science, 2014)
According to the development trend of the act of China's current strategic alliance, this paper elaborates the reason why the success rate of strategic alliance is not high from game theory. The mathematical model based on prisoner's dilemma game and snowdrifts game; synthesize the relevant factors of impacting the revenue sharing of enterprise knowledge alliance. Through analysis, it finds that the strategic alliance is a dynamic process of growth. In each stage of the process, because internal and external environment, business processes, customers, the market reaction and other external conditions as well as internal conditions, such as bearing and sharing mechanisms of the risks and benefits between alliance partners change, which brings enormous difficulties to maintain and develop strategic alliance . Due to the different strategic objectives, work efficiency, learning ability and other conditions, the alliance partners need to pay attention to coordination to make flexible and creative reforms. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4504